2003
DOI: 10.1038/nri1110
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cysteine proteases regulate antigen presentation

Abstract: Antigen presentation by both classical MHC class II molecules and the non-classical MHC class I-like molecule CD1D requires their entry into the endosomal/lysosomal compartment. Lysosomal cysteine proteases constitute an important subset of the enzymes that are present in this compartment and, here, we discuss the role of these proteases in regulating antigen presentation by both MHC class II and CD1D molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
310
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 395 publications
(317 citation statements)
references
References 111 publications
5
310
1
1
Order By: Relevance
“…[1][2][3]. Studies with broad spectrum cysteine protease inhibitors such as leupeptin suggested the involvement of both cysteine and noncysteine proteases (4 -6).…”
mentioning
confidence: 99%
“…[1][2][3]. Studies with broad spectrum cysteine protease inhibitors such as leupeptin suggested the involvement of both cysteine and noncysteine proteases (4 -6).…”
mentioning
confidence: 99%
“…Cathepsin L is a lysosomal protease that plays an important role in the intracellular protein degradation, activation of enzyme precursors, and tumor invasion (8,9). Normally located in lysosomes of mammalian cells, it can be secreted from the cell under certain conditions.…”
mentioning
confidence: 99%
“…To test whether NucNeoR presentation is mediated by a similar pathway, the NeoR and NucNeoR transfectants were incubated for 20 h with 3-MA, a specific inhibitor of autophagosome formation [10], or leupeptin and chloroquine to inhibit lysosomal degradation [13]. After incubation, the inhibitors were removed by repeated washing to preclude interference with T cell functions; the cells were immediately fixed with paraformaldehyde and subsequently probed with the NeoR-specific T cells.…”
Section: Efficient Presentation Of Nuclear Neor On Mhc Class IImentioning
confidence: 99%